Palladium Complexes Based on Ylide‐Functionalized Phosphines (YPhos): Broadly Applicable High‐Performance Precatalysts for the Amination of Aryl Halides at Room Temperature. Issue 19 (28th February 2020) - Tappen, Jens; Rodstein, Ilja; McGuire, Katie; Großjohann, Angela; Löffler, Julian; Scherpf, Thorsten; Gessner, Viktoria H.
Abstract: Palladium allyl, cinnamyl, and indenyl complexes with the ylide‐substituted phosphines Cy3 P + −C − (R)PCy2 (with R=Me (L1 ) or Ph (L2 )) and Cy3 P + −C − (Me)P t Bu2 (L3 ) were prepared and applied as defined precatalysts in C−N coupling reactions. The complexes are highly active in the amination of 4‐chlorotoluene with a series of different amines. Higher yields were observed with the precatalysts in comparison to the in situ generated catalysts. Changes in the ligand structures allowed for improved selectivities by shutting down β‐hydride elimination or diarylation reactions. Particularly, the complexes based on L2 (joYPhos) revealed to be universal precatalysts for various amines and aryl halides. Full conversions to the desired products are reached mostly within 1 h reaction time at room temperature, thus making L2 to one of the most efficient ligands in C−N coupling reactions. The applicability of the catalysts was demonstrated for aryl chlorides, bromides and iodides together with primary and secondary aryl and alkyl amines, including gram‐scale applications also with low catalyst loadings of down to 0.05 mol %. Kinetic studies further demonstrated the outstanding activity of the precatalysts with TOF over 10.000 h −1 . Abstract : User‐friendly and easily accessible Pd complexes of three ylide‐substituted phosphines (YPhos) were prepared and applied in C−N coupling reactions giving way to extremely active catalysts that allow for high yields and selectivities at room temperature for a wide variety of substrates. Aryl chlorides, bromides, and iodides were successfully coupled also in gram‐scale and with low catalyst loadings including difficult substrates, such as alkyl amines.